Morphology and polymorphic phase changes of calcium carbonate micro/nanocrystals using fruit extracts - Ankamwar, Balaprasad (Journal of Nanoscience and Nanotechnology, 2011)
This study reveals the morphology and polymorphic phase changes of calcium carbonate crystals into a mixture of calcite and aragonite micro/nanocrystals of interesting morphology at room temperature by a simple reaction with fruit extracts of Tamarindus indica and Emblica officinalis respectively by mixing CaCO(3) solutions with their corresponding extracts. The control experiments were carried out to establish the plausible role of tartaric acid from Tamarindus indica and ascorbic acid from Emblica officinalis in this regard. The quantitative determination of CaCO(3) phases was done based on the use of intensities obtained from corresponding XRD spectrum. The molar %. of aragonite was found to be more in case of TA and AA rather than TI and EO respectively, however the calcite was observed to be the predominant phase in all four reactions. Interestingly, the TI changes the rhombohedral morphology of calcite to elongated rods, whereas EO induces a great polymorphic phase change.
Keywords: Aragonite; Calcite; Emblica officinalis; Morphology Changes; Polymorphic Changes; Tamarindus indica